EFEITO DE TEMPERATURA, FOTOPERÍODO E SENSIBILIDADE DE Phomopsis amygdali A DIFERENTES PRODUTOS, IN VITRO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The production of peaches in Brazil has suffered production damage due to burning of branches caused by the fungus Phomopsis amygdali. Through experiments in vitro were studied, initially, the best conditions of temperature and photoperiod on the development of the pathogen. Later, under the conditions found, the fungus was subjected to different substances: plant essential oils (eucalyptus, clove, oregano, peppermint, ginger, lemongrass, citronella, rosemary and chamomile); different products extraction plant Calea hispida Baker (quercitrin (CHAM - Acetate methanol), 6-acetyl-7-hydroxy-2,2-dimethylchromene (HCRC - crystals), aqueous extract (CHEA) and essential oil (CHOE)); synthetic fungicides (captan, cyproconazol, tebuconazole, triadimenol, mancozeb and sodium hypochlorite); an inductive resistance (Ascophyllum nodosum) and an insecticide (Bacillus thuringiensis) in order to evaluate the fungistatic effect of these in vitro development of the pathogen. The assessments were made by mean of two measurements, diametrically opposite the colonies daily until seven days after the onset of the experiment. The temperature better favored the development of the pathogen in vitro was 20°C. Have to photoperiod, there was no statistical difference between the treatments tested. It was observed that treatments with essential oils of oregano and lemon grass showed higher antifungal activity against the pathogen when compared to other oils used, highlighting the oregano oil, which completely inhibited growth of the pathogen. The compounds isolated from C. hispida showed low percentage of inhibition of P. amygdali, which did not exceed 21.88%. The fungicides captan, tebuconazole cyproconazol and showed a high level of inhibition relative to the other substances tested. From the concentration of 500 ppm, these fungicides reached 100% of control, showing the most efficient at the fungus control.
Keywords: Prunus persica; cancro do pêssego; controle alternativo; controle químico; Fusicoccum amygdali; Prunus persica; peach cancer; alternative control; chemical control; Fusicoccum amygdali; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA